Scientific Opinion on the safety and efficacy of XTRACT® Evolution‐B, Code X60‐6930 (carvacrol, cinnamaldehyde and capsicum oleoresin), as a feed additive for chickens for fattening. (17th February 2015) - ,; ,
Abstract: The additive XTRACT ® Evolution‐B, Code X60‐6930, is a preparation of carvacrol, cinnamaldehyde and capsicum oleoresin and is intended to be used as a zootechnical feed additive for chickens for fattening. Based on a tolerance study in which chickens for fattening tolerated a 10‐fold overdose of the additive, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concludes that XTRACT is safe for chickens for fattening at the maximum proposed dose (100 mg/kg complete feed). No increase in the exposure of consumers to any of the active substances contained the additive is expected. Therefore, the Panel concludes that use of XTRACT in feed for chickens for fattening under the proposed conditions of use is safe for consumers. It would be prudent to consider the additive to be a skin, eye and respiratory tract irritant and a skin sensitiser. The use of XTRACT at the recommended levels is safe for the environment. XTRACT has the potential to be efficacious in chickens for fattening at the recommended dose of 100 mg/kg complete feed. The use of additive under the proposed conditions does not affect the sensory properties of meat products from chickens.